2013
DOI: 10.2196/jmir.2758
|View full text |Cite
|
Sign up to set email alerts
|

Smartphones as Multimodal Communication Devices to Facilitate Clinical Knowledge Processes: Randomized Controlled Trial

Abstract: BackgroundDespite the widespread use and advancements of mobile technology that facilitate rich communication modes, there is little evidence demonstrating the value of smartphones for effective interclinician communication and knowledge processes.ObjectiveThe objective of this study was to determine the effects of different synchronous smartphone-based modes of communication, such as (1) speech only, (2) speech and images, and (3) speech, images, and image annotation (guided noticing) on the recall and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…Research findings show that students situate their learning by taking the opportunities to gather information as the need arises, evolving into an anytime, anywhere culture. 8 29 This situational opportunistic learning has been reported by others exploring the use of mobile devices in higher education. 27 These authors commented on the necessity of social interactions and learning being critical components of situational learning.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Research findings show that students situate their learning by taking the opportunities to gather information as the need arises, evolving into an anytime, anywhere culture. 8 29 This situational opportunistic learning has been reported by others exploring the use of mobile devices in higher education. 27 These authors commented on the necessity of social interactions and learning being critical components of situational learning.…”
Section: Discussionmentioning
confidence: 66%
“…In medical education, the use of mobile devices has been shown to encourage student learning in, as well as beyond and across the individual situations. 8 Others have shown that although the access to information is rapid, there is a tendency to overuse or even become over-dependent in using mobile devices; this may be inhibiting the internalisation of knowledge, thus leading to the potential for superficial learning. 2 Furthermore, in that study, the participants anticipated that mobile devices would replace the use of traditional textbooks, and that their use would soon be a part of routine clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Multimodal communication facilitated through smartphones connections transfers speech and image at the same time and enhances information recall. [32] Text messaging through the smartphones enhances the speed of message interactions and decreases the need for person-to-person contacts. [33] Whilst the possibilities offered by smartphones for healthcare are promising, it is important to be wary of possible pitfalls.…”
Section: Resultsmentioning
confidence: 99%
“…Older cell phone types have been replaced by the now ubiquitous smartphones, and we have recently entered an era in which everyone owns at least one of these extremely useful and convenient devices. Many advanced functions of these smartphones are being considered for their potential and/or availability for use in actual medical settings [14,15]. Smartphone and tablet apps for educational use have been developed and are becoming more available.…”
Section: Introductionmentioning
confidence: 99%